To Want Is Not Enough: Ethical Duties in Practice, Training, and Research in Community Psychology [Querer No Basta: Deberes Éticos en la Práctica, Formación E Investigación en Psicología Comunitaria] - Pasmanik-Volochinsky, D; Winkler-Muller, M (2012)
The article presents a summary of the results of the research project FONDECYT N° 1080528, which explores the ethical dimension in practice, training, and research in community psychology (CP) in Chile. An intentional opinatic sample of primary (93 participants-users, students, and psychologists-) and secondary information sources (194 documents-programs, courses, theses and codes-) was used. The use of various data collection techniques and qualitative analysis strategies led to the identification of two relevant results: the principle of respect for the other and community participation in identifying and addressing ethical issues. Divergences in the concept of CP and ethical duties in this field were also found. Finally, ethical guidelines for practice, training, and research in CP are suggested. © 2012 by Psykhe.